THE CONCEPT OF CONSTANTS AND VARIABLES IN THE PHILOSOPHY OF ISLAMIC EDUCATION: FROM RELIGIOUS PRINCIPLES TO INTELLECTUAL SCHOOLS - Prihantoro, Hijrian A. (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2018)
The need for education in this age in which we live was occupy a position of the status of necessity, so education is one of the purposes of the Maqashid Sharia, which can not be denied in our social life. Islam as a religion of mercy is known to include all matters of humanitarian issues, including education, while it requires the planning of educational systems to regulate human life in order to achieve the general humanitarian interest. But so far, many educational thinkers have not talked about the concept of the constants and variables in the philosophy of Islamic education. As the researcher at this opportunity, we will talk about that concept by showing its intellectual map through three areas: the fundamentalist field, the relational field and the methodological field. Based on this, it is mentioned that the study in these fields is the focus of research in this research to discover the march of the philosophy of Islamic education from the religious principles to the schools of human thought.